Evaluation of the role of middle ear risk index as a prognostic tool in cases of tympanoplasty in chronic suppurative otitis media - Saidha, Poonam K.; Kapoor, Sahil; Suri, Arpita; Gupta, Ayushi; Kakkar, Vikas (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: In chronic suppurative otitis media (CSOM), the success rate of tympanoplasty, can range from 35% to 92% and is influenced by a number of factors such as age of patient, size and site of perforation, status of ear, ossicular status and surgical technique. The middle ear risk index (MERI) of a CSOM patient is an effective numerical grading system helpful in predicting the outcome of surgery. Methods: A prospective observational study was conducted in 50 patients over a period of 1 year including all cases of CSOM in age group of 18-55 years with conductive hearing loss that underwent tympanoplasty with or without cortical mastoidectomy and role of MERI was analysed for the outcome of the surgery. Results: Successful graft uptake was seen in 92% cases while in 8% cases graft was rejected. Of these 46 cases, 32 cases had mild MERI score, 10 had moderate MERI score and 4 had severe MERI score. It was observed that higher the MERI score, lower the graft uptake. Conclusions: Our study comprised of 50 patients of CSOM which were categorized into mild, moderate and severe on the basis of MERI score preoperatively. All the patients underwent tympanoplasty with or without cortical mastoidectomy and surgical outcome in terms of graft uptake was found to be significant. Higher the MERI score, lower was the graft uptake while lower the MERI score, higher was the graft uptake. Hence, MERI is a useful tool to ascertain the prognosis of tympanoplasty.